Effect of Avocado Pulp on the Quality of Chicken Cutlet - Muthulakshmi, Muthusamy; Rajkumar, Ramasamy; Irsha, Abdul Vahid (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Avocado is a food rich in mono unsaturated fatty acids, tocopherols, phytosterols, phenolic compounds, and procyanidins. In Southern India, avocado (Persea Americana) are frequently used for milkshakes and occasionally added to ice cream and other desserts. The study aimed to evaluate the effect of incorporation of avocado pulp on the physico-chemical, sensory and microbial quality of chicken cutlets. Chicken cutlets were prepared with different levels of avocado pulp, viz., 0% (T1), 5% (T2) and 10 % (T3) and the physico-chemical, sensory and microbial quality of prepared chicken cutlets were assessed. The incorporation of avocado pulp into chicken cutlets reduced the extent of lipid oxidation and microbial count significantly (p < 0.05). In addition, a significant improvement (p < 0.05) in cooking yield and textural properties were also recorded. However, the incorporation of avocado pulp @ 10% in the chicken cutlets showed no significant influence on the overall sensory acceptability of the chicken cutlets.